Viability of Nilem’s Eggs Delayed in Oviposition after The Sign of Spawning - Soeminto Soeminto; Priyo Susatyo; Yulia Sistina (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2006)
This study reports eggs viability from nilem (Osthehilus hasselti CV) parental which their oviposition has been delayed up to 3 – 24 hours from first actual oviposition time. By 3 hours interval, the experimental has been set as completely randomized design with 9 treatments as delay time, i.e. 0, 3, 6, 9, 12, 15, 18, 21 or 24 hours delayed oviposition time, each from three different fish as eggs sources. Results showed that eggs viability were observed from eggs up to 6 hours delayed oviposition treatments from data of fertilization rate of the egg and their larvaes up to 10 days old post hatching. Results from treatment more than 6 hours delayed oviposition showed eggs cleavage, however they never developed further to larvae nor hatching. The 18 hours delayed oviposition eggs groups developed up to first cleavage. Treatment more than 21hours delayed did not showed any cleavage, but cytoplasmic changes were detected. It can be concluded that delayed ovipositions of nilem eggs up to 6 hours delayed did not affected their viability, they developed and hatched as controls one as well as the larvae survive up to 10 days examination. Delayed up to 18 hours incubation although showed some activity, but they were all never developed further than cleavage stage. Key words: Osteochilus hasselti CV, oviposition , eggs and spermatozoon viability